“Computing” and “Information”: Two Paths in “Information Turn” - Wei He (Proceedings, 2021)
The “information turn” has gradually become a new direction in philosophy to replace the “linguistic turn”, with “computing” and “information” as the main paths. The main theories of “computing” path are info-computationalism and Floridi’s philosophy of information; the main theory of “information” path is Wu Kun’s philosophy of information. This paper attempts to explain the modes of operation of the two paths and discriminate and analyze the essential differences between the two paths, which lie in the realization of information based on these three theories.